¿Puede el directorio controlar el deber de Skynet? Repensando el deber de cuidado del directorio en el siglo XXI - Vizcarra Castillo, Raúl (2023)
This article explores the duty of care in the context of the company’s board of directors, in close relation to artificial intelligence. Thus, it highlights the absence of a precedent system in Peruvian corporate law and advocates looking to the case of Delaware, a state that has established solid criteria to implement this duty. Thus, it emphasizes the importance of the board of directors keeping itself informed and establishing mechanisms to supervise the implementation of artificial intelligence, especially in the context of the technological advances in which we find ourselves.Along these lines, a series of recommendations are established, such as the implementation of internal control mechanisms and the appointment of specialized directors. In addition, a re-reading of certain articles of the General Corporations Law is proposed in the light of this need for updating.